Korelasional Kekuatan Otot Perut dengan Kemampuan Heading dalam Permainan Sepak Bola pada Siswa Putra Ekstrakurikuler - Rizad, Tengku (Universitas PGRI Pontianak, 2025)
This study aims to describe the relationship between abdominal muscle strength and heading ability in soccer games among extracurricular students at SMP Negeri 1 Sukadana. The background of this study indicates that abdominal muscle strength is a crucial factor influencing the heading ability of male extracurricular soccer students. However, the reality in the field often shows a lack of awareness among male extracurricular soccer students of the importance of abdominal muscle strength training, which results in less than optimal heading ability. This study generally aims to determine whether there is a relationship between abdominal muscle strength and heading ability in soccer games. Specifically, this study measured the abdominal muscle strength of male extracurricular soccer students in performing sit-ups and their heading ability by performing forward heading movements, and determined the significant relationship between these two variables. The research employed a quantitative descriptive method with a correlational approach. The population consisted of 30 male extracurricular soccer students in grades VIII and IX at SMP Negeri 1 Sukadana, selected using a total sampling technique. Data were collected through tests and measurements, including sit-ups and ball heading ability. Data were analyzed using product-moment correlation. The results showed a significant positive correlation between abdominal muscle strength and heading ability in soccer, with a correlation coefficient (r) of 0.018 and a significance level of 0.670 (p < 0.05). This indicates a strong and significant relationship.